Advanced digital technologies and industrial resilience during the COVID-19 pandemic: A firm-level perspective - Elisa Calza; Alejandro Lavopa; Ligia Zagato (United Nations University (UNU), Maastricht Economic and Social Research Institute on Innovation and Technology (UNU-MERIT), 2022)
The advanced digital production (ADP) technologies of the fourth industrial revolution (4IR) are expected to reshape the way industrial production takes place. These technologies offer new windows of opportunities for developing countries to catch up with the world technological frontier, but, at the same time, they pose new challenges and risks. This paper uses a novel firm-level data set collected by UNIDO and partners around the world to investigate the extent to which these technologies are diffused in developing countries, the main factors supporting their adoption and the role played by these technologies during the COVID-19 pandemic. Three key findings emerge from the analysis: (1) the diffusion of these technologies is still very limited to a handful of firms; (2) large firms, firms operating within global value chains and firms with existing innovative capabilities are more likely to adopt ADP technologies; and (3) advanced digitalization has contributed to the robustness of firms as they address the COVID-19 crisis and supported their readiness to act and respond quickly and adapt to the new context. The findings of the paper are expected to inform policymakers in the design of industrial recovery policies that can strengthen future industrial resilience in developing and emerging economies.
Keywords: O12; O14; O33; 330; Industrial development; digital technologies; resilience; fourth industrial revolution; firm-level analysis; COVID-19